1998
DOI: 10.1144/gsl.sp.1998.139.01.14
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on wave-induced fluid mud streaming at open coasts

Abstract: Wave-induced streaming of fluid mud at open coasts under damped, nonbreaking waves is examined as a likely mechanism to explain nearshore bottom evolution in such an environment. For a two-layered, water-fluid mud domain in which mud is considered to be a viscous continuum, an expression for the streaming velocity is obtained. Preliminary data on alongshore streaming of fluid mud in a wave basin show an order of magnitude agreement with theory. Previous observations on the rates of mud movement along the coast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
(19 reference statements)
1
10
0
Order By: Relevance
“…Fluid mud layers are typically clearly delineated at the top by a lutocline , but the lower interface with the bed is harder to define since that interface may not correspond with the zero‐velocity plane [ Ross and Mehta , ]. Fluid mud viscosity ranges from 2 to 4 orders of magnitude greater than that of water [ Rodriguez and Mehta , ], which has a profound effect on the rheology and therefore the dynamics of the mud itself and on the dynamics of waves traveling overhead [e.g., Mathew et al ., ; Calliari et al ., ; Sheremet et al ., ].…”
Section: Sediment Transportmentioning
confidence: 99%
“…Fluid mud layers are typically clearly delineated at the top by a lutocline , but the lower interface with the bed is harder to define since that interface may not correspond with the zero‐velocity plane [ Ross and Mehta , ]. Fluid mud viscosity ranges from 2 to 4 orders of magnitude greater than that of water [ Rodriguez and Mehta , ], which has a profound effect on the rheology and therefore the dynamics of the mud itself and on the dynamics of waves traveling overhead [e.g., Mathew et al ., ; Calliari et al ., ; Sheremet et al ., ].…”
Section: Sediment Transportmentioning
confidence: 99%
“…The following hydrometeorological factors have been identified to explain such temporal and spatial variability of the shoreline ( Fig. 2): (i) trade-wind wave intensity and direction (Augustinus, 2004;Eisma et al, 1991;Gardel and Gratiot, 2005;Gratiot et al, 2007;Rodriguez and Mehta, 1998), (ii) solitary waves (Wells et al, 1978;Wells and Coleman, 1981a), (iii) the nodal tidal cycle (18.6yrs) Wells and Coleman, 1981b), (iv) tidal and coastal currents (Bourret et al, 2008;Chevalier et al, 2008;Gibbs, 1976;Pujos and Froidefond, 1995), (v) the Northern Atlantic Oscillation (Walcker et al, 2015) and (vi) other secondary factors for which correlations have not been clearly demonstrated, e.g., sea-level variation (NEDECO, 1968;Wong et al, 2009) and irregular ENSO variation Pujos et al, 1996).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…2, the migration of mud banks is driven by several sources of forcing acting at different spatial and temporal scales. Among these forcings, wind-generated waves play a predominant role in longshore transport by liquefying the muddy bottom and by maintaining cohesive sediment in gel-like form (Allison et al, 2000;Augustinus, 2004;Eisma et al, 1991;Gratiot et al, 2007;NEDECO, 1968;Rodriguez andMehta, 1998, Wells et al, 1978;Wells andColeman, 1981a, 1981b). Variability in the rate of migration is influenced by shoreline orientation (Augustinus, 1978;Gardel and Gratiot, 2005), the effects of river flow on mud banks (Anthony et al, 2013;Jolivet et al, 2019), and local shoreline irregularities (Gratiot et al, 2007).…”
Section: Inter-annual Variability Of the Sediment Balancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, the critical parameters of viscosity and shear modulus of the mud, required for their viscoelastic bottom mud model, were obtained from laboratory tests, which may not be representative of real field conditions. More recently, RODRIGUEZ and MEHTA (1998) suggested that based on laboratory investigations the shoreward streaming of mud under monsoonal waves is a plausible mechanism for mud bank formation with the onset of monsoon. LI and PARCHURE (1998) examined the physical factors influencing the suspended sediment concentration profiles and presented a semiempirical model that accounts for the vertical fluxes of fine sediment in suspension due to waves and currents.…”
Section: Introductionmentioning
confidence: 99%